A young immunocompetent patient with spontaneous Aspergillus empyema who developed severe eosinophilia. (2017) - Kudo, Fumiaki; Ohta, Hiromitsu; Nagai, Yoshiaki; Minegishi, Kentaro; Koyama, Shinichiro
Abstract: Aspergillus empyema is usually reported as a complication of surgical procedures, and spontaneous cases are quite rare. Here, we describe the case of a 16-year-old man who suddenly developed dyspnea despite previously being healthy. Chest computed tomography showed multiple mass-containing cavity lesions, pneumothorax, and pleural effusion in the left thorax. Within 2 weeks, Aspergillus fumigatus grew from his pleural effusion, thus he was diagnosed with Aspergillus empyema. He also developed severe eosinophilia after admission, and was treated with anti-fungal drugs. Although there are many factors that can cause eosinophilia, we suspect that infection with Aspergillus fumigatus was the major cause of the eosinophilia in this patient. The lack of bronchial symptoms and lesions were not consistent with a diagnosis of allergic bronchopulmonary aspergillosis. As far as we know, this is the first case of spontaneous Aspergillus empyema resulting in severe eosinophilia.